On-the-Road Driver Behavior Experimentation: Issues and Approaches. (September 2013) - Lerner, Neil; Chrysler, Susan; Cooper, Joel; Jenness, James; Manser, Michael; Reimer, Bryan
This panel addresses a research methodology that is becoming more essential for driving safety research. The methods of driving simulation and naturalistic driving have been prominent and remain important, but their limitations are becoming more evident. On-the-road experimental methods offer some of the advantages of naturalistic driving while providing a degree of experimental control and manipulation more typical of simulator experiments. Five expert researchers will discuss both scientific and pragmatic issues in the conduct of on-the-road experimentation, making use of lessons learned from their own studies. Each panelist will present a brief perspective on the problem from the point of view of their experience and expertise. This will be followed by an open discussion period.